Student Review Box for Teacher Performance Assessment - Fatma Rahman; Novita Hulopi; Putri Jesica Damapolii Lili Suarn; Abdul Rahmat (Global Scientific Publishing, 2022)
This review box is intended as a medium for assessing teacher performance to students. Where we can see the problem, every student in receiving learning has an impact on the teacher who teaches, therefore this review box is very important in assessing teacher teaching to students. By making creative learning effective, besides teacher students are also expected to be able to recognize the character of a teacher in carrying out the teaching process in the classroom. Students can understand effective learning to develop aspects of the physical, cognitive, emotional and social development of students. This study used the direct observation method, in which project activities were carried out by directly observing SDN 43 Hulonthalangi. Where this research was conducted by making a "review box" media made from used cardboard and waste paper. On average, students from grades 1 to 4 are very creative in making media that has been made in groups. The result of the research is that each group has its own characteristics in their work. Each student is able to express and imagine according to what they see. Students are also able to work well together with their group mates
Keywords: Review Box; Performance; Rating